THE EFFECT OF LAMTORO (LEUCAENA LEUCOCEPHALA) LITTER AND BLACK SOLDIER FLY (HERMATIA ILLUCENS) KASGOT AND THE ADDITION OF ARBUSCULAR MYCORRHIZA ON GROWTH VARIABLES OF TOMATO PLANTS (LYCOPERSICUM ESCULENTUM MILL.) SERVO F1 VARIETIES - Rezky, Putri
Tomatoes are a much-needed horticultural commodity in Indonesia for various food processing, medicines, and cosmetics. Based on the Central Bureau of Statistics, tomato consumption by the household sector in 2021 increased by 6.93 percent from 2020, reaching 677.97 thousand tons, which is in line with the increase in tomato production figures. Regarding the utilization of polybag-based media to overcome land limitations, nutrients in polybags are provided in a limited manner and are easily compressed. Therefore, it is necessary to add organic materials along with microbial agents that help in providing nutrients for plants and maintaining the physical-chemical conditions of the media during cultivation. This study aims to analyze the effect of the treatment of variations in the stratification/layering planting media model with the addition of lamtoro and kasgot litter organic materials in polybag media, variations in mycorrhiza doses, and the interaction of the two factors on plant growth variables, determine the treatment that gives the best results, and analyze the effect of the stratification and mycorrhiza planting media model on the physical and chemical quality of the media at the end of tomato cultivation of the Servo F1 variety. The research was conducted from October 2022 to January 2023 at the Main Seedling Farm of PT East West Seed Indoneisa, Campaka District, Purwakarta Regency, West Java. There were 16 treatment units with 10 random sample plants each. The research method is divided into the process of cultivating tomato plants and testing the physical and chemical parameters of all treatment units. Testing of physical parameters of the media was carried out at PT East West Seed Indonesia, while testing of chemical parameters of the media was carried out at the Soil Laboratory of Padjajaran University. Data were analyzed using ANOVA Two Ways test and Tukey BSD at 95% confidence level (?=0.05). The results showed that stratified planting media gave a significant effect on tomato plant height at 3 weeks after planting (highest in A3), then on stem diameter at 3 weeks after planting (highest in A0) and 5 weeks after planting (highest in A0), and did not give a significant difference on leaf area, root dry weight, and early flowering age. Application of mycorrhiza at a dose of 15 g/plant (B2) gave a significant effect on plant height and did not show a significant effect on other variables. The interaction of the two treatments did not give a significantly different effect on the results of all growth variables in this study. The best combination of planting media for growth variables of Servo F1 tomato plants is A0 and A3 with the addition of mycorrhiza B2 as much as 15 g/plant; and the overall physical quality of the media was not found to be compacted media, with the value of content weight and porosity showing loose media. The best chemical quality of the media is owned by the A1 treatment code with or without the addition of mycorrhiza, then followed by A3, A2, and A0.